Influence of unilateral maxillary first molar extraction treatment on second and third molar inclination in Class II subdivision patients. - Livas, Christos; Pandis, Nikolaos; Booij, Johan Willem; Halazonetis, Demetrios J; Katsaros, Christos; Ren, Yijin (Angle Orthod, 2016)
OBJECTIVE: To assess the maxillary second molar (M2) and third molar (M3) inclination following orthodontic treatment of Class II subdivision malocclusion with unilateral maxillary first molar (M1) extraction. MATERIALS AND METHODS: Panoramic radiographs of 21 Class II subdivision adolescents (eight boys, 13 girls; mean age, 12.8 years; standard deviation, 1.7 years) before treatment, after treatment with extraction of one maxillary first molar and Begg appliances and after at least 1.8 years in retention were retrospectively collected from a private practice. M2 and M3 inclination angles (M2/ITP, M2/IOP, M3/ITP, M3/IOP), constructed by intertuberosity (ITP) and interorbital planes (IOP), were calculated for the extracted and nonextracted segments. Random effects regression analysis was performed to evaluate the effect on the molar angulation of extraction, time, and gender after adjusting for baseline measurements. RESULTS: Time and extraction status were significant predictors for M2 angulation. M2/ITP and M2/IOP decreased by 4.04 (95% confidence interval [CI]: -6.93, 1.16; P  =  .001) and 3.67 (95% CI: -6.76, -0.58; P  =  .020) in the extraction group compared to the nonextraction group after adjusting for time and gender. The adjusted analysis showed that extraction was the only predictor for M3 angulation that reached statistical significance. M3 mesial inclination increased by 7.38° (95% CI: -11.2, -3.54; P < .001) and 7.33° (95% CI: -11.48, -3.19; P  =  .001). CONCLUSIONS: M2 and M3 uprighting significantly improved in the extraction side after orthodontic treatment with unilateral maxillary M1 extraction. There was a significant increase in mesial tipping of maxillary second molar crowns over time.
Keywords: Adolescent; Cephalometry; Child; Dental Occlusion; Female; Humans; Male; Maxilla; Molar; Molar, Third; Tooth Extraction; Tooth Movement Techniques